Sex Differences in Clinical Characteristics and Outcomes in Elderly Patients With Heart Failure and Preserved Ejection Fraction: The Irbesartan in Heart Failure With Preserved Ejection Fraction (I-PRESERVE) Trial - Lam, Carolyn S.P. (Circ Heart Fail, 2012)
BACKGROUND: There are few sex-specific outcome data in heart failure with preserved ejection fraction. METHODS AND RESULTS: We assessed sex differences in baseline characteristics and outcomes among 4128 patients with heart failure with preserved ejection fraction in the Irbesartan in Heart Failure with Preserved Ejection Fraction (I-PRESERVE) trial. Women (n=2491) with heart failure with preserved ejection fraction were ≈1 year older (72±7 years versus 71±7 years) and more likely to be obese (46% versus 35%) and have chronic kidney disease (34% versus 26%) and hypertension (91% versus 85%) than men but less likely to have an ischemic cause (19% versus 34%), atrial fibrillation (27% versus 33%), or chronic obstructive pulmonary disease (8% versus 13%) (all P<0.001). During a mean of 49.5 months, there were 881 deaths (447 in women, 434 in men; risk ratio, 0.64; 95% CI, 0.56–0.74) and 5776 hospitalizations (3239 in women, 2537 in men; risk ratio, 0.80; 95% CI, 0.76–0.84). Women had lower risk of all-cause events (deaths and hospitalizations), even after adjusting for baseline characteristics (adjusted hazards ratio, 0.81; 95% CI, 0.73–0.89). However, the sex-related difference in risk of all-cause events was modified in the presence or absence of atrial fibrillation, renal dysfunction, stable angina pectoris, or advanced New York Heart Association class symptoms. CONCLUSIONS: In patients with typical heart failure with preserved ejection fraction, there were prominent sex differences in baseline characteristics and outcomes. Women had better overall prognosis, although the presence of 4 common baseline characteristics seemed to moderate this finding. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT000095238.